The Effectiveness of the Questioning, Answering, Sharing, Extending, and Evaluating Learning Model on Improving Students Critical Thinking Skills - Ahmad Yani; Adriani Adriani; Muhammad Arafah; Ambo Upe; Siti Darwa Suryani (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to examine the efficacy of the QASEE learning model in increasing critical thinking abilities of students in class XI at UPT SMA Negeri 6 Wajo. This study was carried out at SMA Negeri 6 Wajo during the academic year 2021/2022. The sample strategy employed is a basic random sampling method with a quasi-experimental design pattern with nonequivalent control groups. Essay exams were used to collect data on critical thinking abilities. The acquired data was then examined using the ANOVA test. Data study using the SPSS 26 for Windows tool reveals that the QASEE learning model has an impact on developing students' critical thinking abilities. The experimental class's N-Gain value for critical thinking abilities is 0.71, whereas the control class's N-Gain value is 0.42. Based on the ANOVA test findings, the significant value of critical thinking skills is less than 0.05, indicating that the QASEE learning model has an impact on increasing students' critical thinking abilities.